Inventors, patents and invenctive activities in the English brewing industry, 1634-1850 - Alessandro Nuvolari; James Summer (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2012)
This paper examines the relationship between patents, appropriability strategies and market for technologies in the English brewing industry before 1850. Previous research has pointed to the apparent oddity that large-scale brewing in this period was characterized both by a self-aware culture of rapid technological innovation, and by a remarkably low propensity to patent. Our study records how brewery innovators pursued a wide variety of highly distinct appropriability strategies, including secrecy, selective revealing, patenting, and open innovation and knowledge-sharing for reputational reasons. All these strategies could co-exist, although some brewery insiders maintaineda suspicion of the promoters of patent technologies which faded only in the nineteenth century. Furthermore, we find evidence that sophisticated strategies of selective revealing could support trade in inventions even without the use of the patent system.
Keywords: N73; O34; 330